Moving (the focus) from denial to dialogue: The recommended directions for communicating climate change to non-expert audiences based on the analysis of climate scientists’ communicative experiences - Mytych, Jagoda (Quaestiones Geographicae, 2024)
The article’s topic reflects climate scientists’ presence and communication in the public sphere, while the main focus is on the two ways a society may respond to the climate scientists’ communicative efforts: by denying the scientific messaging (climate change denial) and by engaging in relation-building communication (climate change dialogue). Those aspects were explored from the point of view of American and Polish climate scientists through the method of in-depth interviewing. According to the scientists, as the study results show, the most effective way to enhance science-society dialogue on climate change is to detangle from unproductive denial narratives and truly embrace the dialogic model of science communication by opening it to feedback, including honest societal scepticism.